Language education policy at schools in the era of Southeast Asian economic community integration - MOCHTAR MARHUM (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The type of research into how the integration of the Southeast Asian Economic Community has influenced language education policy implementation. The students and teachers of Central Sulawesi Province, Eastern Indonesia, were surveyed. The government mandates instruction in both English and Bahasa Indonesia, the national language, and other local languages.Method: Three primary methods were used in the researcher’s qualitative methodology. The three main methods are in-person interviews, in-depth observations, and thorough records. English language learning and study are on the rise, as evidenced by the study’s findings.Findings: The majority of participants in the integration of the Southeast Asian Economic Community think that English should develop into a functional language of communication. Many people in Southeast Asian countries speak Malay, so that language is often suggested as a possible replacement for Lingua Franca. Foreigners coming to Indonesia on business must learn the language spoken there to communicate effectively with locals and be accepted into local society. Kids must learn to speak the language they were raised in at school.Implications/Novel Contribution: Policy decisions about how languages are taught should have positive consequences for students preparing for Southeast Asian Economic Integration.